The distinctive material cycle associated with seabirds and land crabs on a pristine oceanic island: a case study of Minamiiwoto, Ogasawara Islands, subtropical Japan - Sato, Nozomu; Nakashita, Rumiko; Sasaki, Tetsuro; Kato, Hidetoshi; Karube, Haruki; Mori, Hideaki; Kawakami, Kazuto (Oecologia, 2025)
Seabirds are responsible for transporting marine material to oceanic islands, and attempts are being made to restore their function on many islands where they have become extinct. However, little is known about the original island ecosystems prior to disturbance. Minamiiwoto, located in the Ogasawara Islands, is an uninhabited oceanic island that remains uninvaded by alien animals, and its pristine ecosystem and material cycle should serve as a reference for the restoration of disturbed island ecosystems. We analyzed the food web structure of several of the Ogasawara Islands with different disturbance intensities using stable isotopes (δ 13 C, δ 15 N) and compared the characteristics of the material cycle. We found that seabirds and land crabs are distributed across the entire island of Minamiiwoto, with high δ 15 N values derived from marine resources and a gradient in the δ 15 N of land crabs reflecting differences in seabird species with elevation. In contrast, on islands where forest-nesting seabirds have been extinct for more than 50 years, the nutrient supply to the island interior has been lost, and the δ 15 N of most organisms was significantly lower. Isotopic food niches among predators were clearly partitioned by species (max. 14% overlap) on Minamiiwoto, while on the disturbed islands they tended to be highly similar (max. 53% overlap). Our results confirmed that Minamiiwoto still maintains a pristine ecosystem characterized by material transport by seabirds and decomposition by land crabs. The recovery of these biological functions should be the guide for conservation and restoration of oceanic islands subjected to anthropogenic disturbance.